An expert consensus to standardise the assessment of histological disease activity in Crohn's disease clinical trials. Issue 7 (7th January 2021) - Almradi, Ahmed; Ma, Christopher; D'Haens, Geert R.; Sandborn, William J.; Parker, Claire E.; Guizzetti, Leonardo; Borralho Nunes, Paula; De Hertogh, Gert; Feakins, Roger M.; Khanna, Reena; Lauwers, Gregory Y.; Mookhoek, Aart; et al.
Summary: Background: Targeting histological remission or response in Crohn's disease (CD) is not recommended in clinical practice guidelines or as an outcome in clinical trials due to uncertainties regarding index validity and prognostic relevance. Aims: To conduct a modified RAND/University of California Los Angeles appropriateness process with the goal of producing a framework to standardise histological assessment of CD activity in clinical trials. Methods: A total of 115 statements generated from literature review and expert opinion were rated on a scale of 1‐9 by a panel of 11 histopathologists and 6 gastroenterologists. Statements were classified as inappropriate, uncertain or appropriate based upon the median panel rating and degree of disagreement. Results: The panellists considered it important to measure histological activity in clinical trials to determine efficacy and that absence of neutrophilic inflammation is an appropriate histological target. They were uncertain whether the Global Histological Activity Score was an appropriate instrument for measuring histological activity. The Geboes Score and Robarts Histopathology Index were considered appropriate. Two biopsies from five segments should be biopsied, and the colon and the ileum should be analysed separately for all indices. Endoscopic mucosal appearance should guide biopsy procurement site with biopsies taken from the ulcer edge, or the most macroscopically inflamed area in the absence of ulcers. Conclusion: We evaluated the appropriateness of items for assessing histological disease activity in CD clinical trials. These items will be used to develop a novel histological index. Abstract : Absence of neutrophilic infiltrate was considered an appropriate target. The Geboes score and Robarts Histopathological Index was considered appropriate. Two biopsies should be taken from the ileum and each colonic segment.